2019
DOI: 10.1186/s13636-019-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

Replay attack detection with auditory filter-based relative phase features

Abstract: There are many studies on detecting human speech from artificially generated speech and automatic speaker verification (ASV) that aim to detect and identify whether the given speech belongs to a given speaker. Recent studies demonstrate the success of the relative phase (RP) feature in speaker recognition/verification and the detection of synthesized speech and converted speech. However, there are few studies that focus on the RP feature for replay attack detection. In this paper, we improve the discriminating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…By comparing the proposed LPR-RP/LPAES-RP with the LPR-MFCC, we noticed that the phase-based feature provided encouraging performance for replay attack detection. Likewise, the LFMGDCC in [41] and DCT-linear-RPS in [41], IFCC [33], mel-RP in [36], and gammatone-RP in [39] were confirmed to be efficient phase features under unseen evaluation. However, the LFMGDCC feature may lose some representation in the vocal source information of the given speech due to the enhancements of the envelope of the short-time speech spectrum, and the phase shift variation in the DCT-Linear-RPS is not normalized by cutting positions.…”
Section: B Results On the Evaluation Subsetmentioning
confidence: 91%
See 2 more Smart Citations
“…By comparing the proposed LPR-RP/LPAES-RP with the LPR-MFCC, we noticed that the phase-based feature provided encouraging performance for replay attack detection. Likewise, the LFMGDCC in [41] and DCT-linear-RPS in [41], IFCC [33], mel-RP in [36], and gammatone-RP in [39] were confirmed to be efficient phase features under unseen evaluation. However, the LFMGDCC feature may lose some representation in the vocal source information of the given speech due to the enhancements of the envelope of the short-time speech spectrum, and the phase shift variation in the DCT-Linear-RPS is not normalized by cutting positions.…”
Section: B Results On the Evaluation Subsetmentioning
confidence: 91%
“…Although the RP has been successfully implemented for spoofing attack detection, its discriminating ability for replay attack detection can be further improved using a frequency resolution. In our previous work [36]- [39], mel/inverted mel-scale filterbank, linear-scale filterbank, attention-based adaptive filterbank, and gammatone-scale filterbank were applied to convert the RP information from the original linear scale to new scales (such as mel-scale, inverted mel-scale, and gammatone-scale), where the modified RP information is called mel-scale RP [37], inverted mel-scale RP (IMel-RP) [36], linear-scale RP (linear-RP) [36], adaptive scale RP (ARP) [38], gammatone-scale RP (gamatone-RP) [39], respectively. The results demonstrated that the mel-RP, ARP, and gammatone-RP outperformed the original RP feature due to the frequency resolution of the filterbank.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the antispoofing competition ASV2017 [31], Witkowski, et al [32] pointed out that replay attacks can be detected by analyzing the high-frequency band of the replayed recordings. Zeyan et al [33] improved the discriminating ability of the relative phase (RP) features by proposing two new auditory filterbased RP features for replay attack detection. To detect the remote attaker, Lee et al [12] proposed a sonar-based liveness detection system.…”
Section: A Audible Attack On Vcssmentioning
confidence: 99%
“…To utilize the phase information, Tom et al [18] used the group delay function (GD) in replay detection. Oo et al [19] introduced the relative phase (RP) feature and further extended it in the Mel-scale (Mel-RP) and the gammatone-scale (Gamma-RP). Phapatanaburi et al [20] proposed to extract RP based on the linear prediction analysis (LPA), which extracted RP on the residual signal of LPA.…”
Section: I R E L a T E D W O R Kmentioning
confidence: 99%